Springer handbook of geographic information - Danko, David M.; Kresse, Wolfgang , 1954- (Springer, 2012)
This handbook includes separate sections on Basics and Applications, offering the reader a comprehensive view on Geographic Information. For ideal thematic separation the Basics are split into the sections Computer Science and Geoinformatics